2019
DOI: 10.1016/j.wem.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Acetazolamide Dosing in Countering Altitude Illness: A Comparison of 62.5 vs 125 mg (the RADICAL Trial)

Abstract: Introduction-North American guidelines propose 125 mg acetazolamide twice daily as the recommended prophylactic dose to prevent acute mountain sickness (AMS). To our knowledge, a dose lower than 125 mg twice daily has not been studied. Methods-We conducted a prospective, double-blind, randomized, noninferiority trial of trekkers to Everest Base Camp in Nepal. Participants received the reduced dose of 62.5 mg twice daily or the standard dose of 125 mg twice daily. Primary outcome was incidence of AMS, and secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…A meta‐analysis on effective AZ doses in AMS prophylaxis published in 2012 showed that doses of 750, 500 and 250 mg day −1 were all effective in preventing AMS (Low, Avery, Gupta, Schedlbauer, & Grocott, ). According to a recent report, even lower doses (125 and 62.5 mg day −1 ) reduced the incidence of AMS (McIntosh et al., ). It is likely, therefore, that we used a higher AZ dose than necessary, although 250 mg three times daily is not unusual in clinical practice (Adamson & Swenson, ) and in AMS prophylaxis (Kayser et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis on effective AZ doses in AMS prophylaxis published in 2012 showed that doses of 750, 500 and 250 mg day −1 were all effective in preventing AMS (Low, Avery, Gupta, Schedlbauer, & Grocott, ). According to a recent report, even lower doses (125 and 62.5 mg day −1 ) reduced the incidence of AMS (McIntosh et al., ). It is likely, therefore, that we used a higher AZ dose than necessary, although 250 mg three times daily is not unusual in clinical practice (Adamson & Swenson, ) and in AMS prophylaxis (Kayser et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although doses up to 750 mg daily are effective at preventing AMS compared to placebo, they are associated with more frequent and/or pronounced side effects, do not convey greater efficacy, and are not recommended for prevention. A recent, small study suggested that 62.5 mg every 12 h was noninferior to 125 mg every 12 h, 26 but further research with greater numbers of participants in different high altitude settings should be completed before a change in dose can be recommended. The pediatric dose of acetazolamide is 2.5 mg$kg -1 $dose -1 (maximum 125 mg$dose -1 ) every 12 h. 27 Recommendation.…”
Section: Acetazolamidementioning
confidence: 99%
“…Nýleg rannsókn sýndi að lágur skammtur, 62,5 mg tvisvar á dag, hafði ekki síðri verkun en 125 mg af asetasólamíði tvisvar á dag. 53 Byrjað er að taka lyfið sólarhring fyrir haeðaraukningu og haett þegar aftur er komið niður fyrir 2500 m, eða ef staldrað er við í sömu haeð í meira en 4-5 sólarhringa 7 Ekki má gefa asetasólamíð þeim sem hafa ofnaemi fyrir súlfalyfjum vegna mögulegs krossofnaemis. 7 Til að ganga skugga um að lyfið þolist vel er maelt með að prófa lyfið við sjávarmál um tveimur vikum fyrir áaetlaða notkun.…”
Section: Haeðarveiki Og Haeðarheilabjúgurunclassified